A study of micro RNA profiles in ischaemic stroke and its risk factor in development of the novel biomarker of young stroke patients / Gan Chye Sheng - Gan, Chye Sheng (2012)

(untitled)
Recent global stroke surveillance conducted by World Health Organization (WHO) has reported 15 million people suffer from stroke per annum. Approximately one-third of the stroke causes mortality placing it as the second leading cause of death after cardiac arrest. Knowledge pertaining stroke has been valuable and utmost desired in order to deliver effective education, prevention, diagnosis/classification and management. Emergence of microRNA expression level delivering promising biomarker has driven diligent researches in developing novel biomarkers for stroke. MicroRNA is a class of ~22 nucleotide-long non-coding RNAs, which is shown to orchestrate protein expression at posttranscriptional levels, hence earlier detection prior manifestation. Acquiring the-state-of-the-art Real-time PCR technology in RNA quantification, this study was aimed to study the microRNA-145, -214, -222, -223, -23b and -339 present in peripheral blood and its temporal expression profiles of chronic young ischaemic stroke patients; having an insight of the molecular regulation of cerebrovascular maladies origin. Peripheral blood of chronic ischaemic stroke patients (n = 32) aged between 18-49 years, characterized based on WHO clinical criteria which subsequently classified in accordance to TOAST guideline were tested in this study. Subsequent peripheral blood sampling of these patients (n = 11) were performed between 3 to 16 months after the initial sampling in order to study the long-term stroke temporal expression profiles of each microRNAs studied. Peripheral blood form normal volunteers (n = 14) were used as controls. Ribosomal RNA, 18S rRNA expression was used as housekeeping gene. Students’ t-Test was employed for statistical calculation. P value of lesser then 0.05 (p < 0.05) is considered significant. Results revealed the circulating microRNA-145, -222, -223 and -23b that are implicated in the vascular biology and immune response in young ischaemic stroke patients demonstrated ectopic iii expression profile relative to the normal control. The temporal expression profile of circulating microRNA-214, -222, -223 and -23b demonstrated plummet in expression; this suggests recovery and downregulation of microRNAs expression is associated with good outcome following stroke. Comparative analysis of the 6 circulating microRNAs and the subtypes of ischaemic stroke suggested that the microRNA-145, 223, 23b and 339 expression profile in cardioembolic subtype of stroke might differ from the atherosclerotic stroke that comprises of large and small vessel subtypes. In addition, the expression profile of circulating microRNA-23b was also shown to be significantly different between the cardioembolic and undetermined subtypes of ischaemic stroke. Therefore, this study demonstrates the potential of peripheral blood microRNAs to be developed as diagnostic and prognostic biomarkers of cerebral ischaemic stroke.